THE USE OF STATED PREFERENCE TECHNIQUE TO MODEL MODAL CHOICES - Resdian syah (KURVATEK, 2016)
Public transportation especially bus services in Kuching City, Malaysia are relatively old and most of the buses are in state of dilapidation. This gives a very bad image on Kuching city and poor perception especially from the tourists and local consumers. To achieve a sustainable public transport industry, the old buses need to be regenerated and replaced with modern buses. The aim of the study is to explore the consumer’s travel behavior by employing modal choice modelling. Consequently, a study was conducted in Kuching City Area by using stated preference technique, analyzed and compiled by using SPSS.17 multiple linear regressions analysis. In this context, discrete choice analysis was used to examine the relationship between independent variables (travel time, waiting time, fares and comfort) and dependent variables (choice of respondent whether to consume old bus or choose new bus services). A total of 2000 respondents were interviewed. The findings showed that for the trips purpose, fares and comfortability were the primary factors that reflected the decision or behavior of the respondents asked. It was discovered that there is a significant relationship between the choice of the respondents and comfortability. For the trips purpose to school, recreation, shopping and others, most of the respondents preferred to opt for scenario 5 (travel time 20 min, frequency 20 min, fare RM 2.00, and the level of comfort is good with AC system) which gave the highest demand with the percentage of 75.4%, 55.1%, 70.3% and 69.1% respectively. On the other hand, scenario 3 (travel time 30 min, frequency 15 min, fare RM 2.00, and the level of comfort is good with AC system) was chosen for the purpose of working trips with the percentage of 50.5% respectively. Thus, it can be concluded that scenario 5 is the most appropriate condition to be implemented for the future bus services to serve the consumers in Kuching city subjected to a condition whereby the bus operators need to deliver a better, comfortable and reasonable fares bus services. It also appeared that longer travel time did not affect for the travelers choice at this stage. Hence, the study suggests that the local authority and the bus operators should establish a “quality partnership” and working together in order to come out with a much better and appropriate transport policy and schemes for the existing public transportation systems, especially bus services.